GAYA KEPEMIMPINAN TRANSFORMASIONAL, GAYA KEPEMIMPINAN TRANSAKSIONAL DAN BUDAYA ORGANISASI TERHADAP KEPUASAAN KERJA KARYAWAN (STUDI PADA KARYAWAN TIDAK TETAP BANK ABC HARAPAN INDAH BEKASI) - Amanda Ernita; Ahmad Adriansyah (Ibs Press, 2023)
The spread of the Covid-19 virus harms the industry in Indonesia. One of the industries that have been affected by Covid-19 is banking. Human resource management is a central element of the banking industry, so the position of employees in the organization has a strategic role. HR optimization must be equipped with expectations and move the organization to meet its satisfaction. Job satisfaction is very influential on performance; if someone gets high job satisfaction, it will impact his performance. This research starts from July 2021 to February 2022 with primary data. This research samples is employees of the Bank ABC Harapan Indah Bekasi branch were selected using non probability sampling techniques and sampling purposive.The results of this study have implications for management, practitioners, and academics, namely the need to consider job satisfaction for non-permanent employees at the Bank ABC Harapan Indah Bekasi branch.